2006
DOI: 10.1542/peds.2005-0795
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Steroids and Oral Leukotriene Modifier Therapy in Residual Sleep-Disordered Breathing After Tonsillectomy and Adenoidectomy in Children

Abstract: Financial Disclosure: Drs Kheirandish and Gozal are the recipients of an investigator-initiated grant from Astra Zeneca Ltd for an unrelated research project on the effect of intranasal budesonide in mild sleepdisordered breathing in children. Dr Gozal serves on the national speaker bureau of Merck. ABSTRACTOBJECTIVE. Tonsillectomy and adenoidectomy (T&A) is the primary therapeutic approach for sleep-disordered breathing (SDB) in children. However, residual mild SDB will be found in more than one third of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
105
0
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(119 citation statements)
references
References 49 publications
0
105
0
14
Order By: Relevance
“…They observed that the combined therapy was effective and reported that surgery might be replaced by antiinflammatory therapy in patients with mild obstructive sleep apnea (OSAS) or postoperative residual OSA (29). In a study by Khirandish with 22 patients, a combination of budesonide and montelukast was administered for 12 weeks for OSAS due to residual adenoid tissue following adenotonsillectomy and a significant improvement in the apnea hypopnea index was found (30). According to our results, the combination therapy is effective at reducing adenoid size, but superiority over montelukast or steroid alone could not be established.…”
Section: Discussionmentioning
confidence: 66%
“…They observed that the combined therapy was effective and reported that surgery might be replaced by antiinflammatory therapy in patients with mild obstructive sleep apnea (OSAS) or postoperative residual OSA (29). In a study by Khirandish with 22 patients, a combination of budesonide and montelukast was administered for 12 weeks for OSAS due to residual adenoid tissue following adenotonsillectomy and a significant improvement in the apnea hypopnea index was found (30). According to our results, the combination therapy is effective at reducing adenoid size, but superiority over montelukast or steroid alone could not be established.…”
Section: Discussionmentioning
confidence: 66%
“…Finally, an association of the above (antileukotrienes and intranasal corticosteroids) was tested in children with mild residual OSAHS (AHI 1-5/h) following adenotonsillectomy 6 . All 4 study indices (apnea, apnea/ hypopnea, micro-arousal and lowest percutaneous arterial oxygen saturation during sleep) were significantly improved in the treatment group (n = 22) compared to the group without treatment (n = 14).…”
Section: Antileukotriene Agents Indications For Medical Treatmentmentioning
confidence: 99%
“…It has been reported that there is increased expression of leukotriene receptors in adenotonsillar tissue of children with OSA [67]. In clinical trials, montelukast was effective in improving sleep-disordered breathing as both a first-line therapy for mild OSA and as a second-line treatment (in combination with nasal steroids) for residual OSA after adenotonsillectomy [68,69].…”
Section: Montelukastmentioning
confidence: 99%